Exploring the impact of stimulus transparency in ERP-BCI under RSVP. - Fernández-Rodríguez, Álvaro; Velasco-Álvarez, Francisco Javier; Alvarez, Chloé; Langin, Célia; Letouzé, Théodore; André, Jean-Marc; Ron-Angevin, Ricardo (ACM Library Digital, 2024)
Rapid serial visual presentation (RSVP) is currently one of the most suitable paradigms for implementing a visual brain–computer interface based on event-related potentials (ERP-BCI) for patients with limited ocular motility. This paradigm presents stimuli centered in the user’s field of vision, which may hinder the patient from attending to other elements on the screen. A potential solution to this could be the use of semi-transparent stimuli, allowing both the stimulus and the background to be perceived. Therefore, the objective of this study is to evaluate the impact of stimulus transparency on ERP-BCI performance under the RSVP paradigm. Five participants tested the ERP-BCI under RSVP using three different stimulus transparencies with alpha channels set to 255 (C1), 85 (C2), and 28 (C3). The results showed the following average BCI classification accuracies: C1, 70%; C2, 74.67%; and C3, 60.67%. Although the analyses did not reveal significant differences, the results suggest that the transparency level should be carefully manipulated to maintain a balance between stimulus transparency and performance, with C2 even exhibiting the highest accuracy among the conditions. This finding should be considered by future ERP-BCI proposals aimed at users who need gaze-independent systems.
Política de acceso abierto tomada de: https://authors.acm.org/author-resources/author-rights
Keywords: Interfaces cerebro-ordenador; Event-related potential (ERP); Brain-computer interface (BCI); Rapid serial visual presentation (RSVP); Stimulus; Transparency